Rasgos de la personalidad y femicidio en una persona privada de libertad del centro penitenciario Quevedo - Sanchez Aguilar, María Jose (2019)
The present work explains the features of the Psychopathological Personality of Femicide, through the case study, in which a 21-year-old male subject was sentenced by the Ecuadorian Prosecutor's Office for the murder crime of a woman of the same age, this event occurred in the city of Quevedo, province of Los Ríos on August 16, 2017. With the reinforcement of psychodiagnostic techniques, a profile of the subject is managed. Psychopathological features of his personality are recounted, a proposal of psychotherapy aimed at addressing his problem is also elaborated. The exploration was carried out in the Penitentiary Center in Quevedo, under the case study methodology, which the inmate provided his collaboration to be part of the present investigation, and is also serving a prison term for the commission of the crime of femicide